Evaluating the Effect of Addition of Titanium Dioxide Nanoparticle on Some Physical Properties of Flowable Composite Resin - Sazgar Srbast Qasim1 , Diyar Khalid Bakr2 , Dara H. Rasheed3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objective: The flowable dental composite resins were introduced to the dental specialty because of theadvantages they possess over the conventional composite resins. The use of nanotechnology in the dentistryfield is one of the growing innovations in recent years. The aim of the present study was to evaluate certainphysical properties of flowable dental composite after incorporation of titanium dioxide nanoparticles(TiO2NPs).Materials and Methods: In the present study, TiO2NPs at 1.25 % and 2.5% concentrations were added toflowable composite, while the unmodified composite was used as control. Then the physical properties of thecontrol and modified composite resins, including flowablity, radiopacity and water sorption and solubilitywere tested. Data were analyzed with One way ANOVA, using SPSS 20.Results: The results showed that there was statistically significant difference among the tested groupsregarding flowability and radiopacity (P<0.05). In addition, there was no significant difference amongcontrol group and TiO2 modified groups regarding water sorption and solubility.Conclusion: Based on the results of the present study, a flowable dental composite was successfullyreinforced with TiO2. Incorporation of small weight percentages of this nanofiller exhibited propertiessimilar to the control material regarding water sorption and solubility. The flowability was slightly reducedand radiopacity of the reinforced composites was increased, these changes were acceptable for clinicalapplications and below ISO standards limits.